The Architecture of the Archbishopric of Ohrid in the 13th–14th Centuries - Zavorina, Maria L. (Actual Problems of Theory and History of Art, 2024)
The article attempts to present a comprehensive picture of the development of architecture in the lands under the jurisdiction of the Ohrid Archbishopric in the 13th–14th centuries. At that time, during the constant military clashes during the rivalry of the Byzantine and Slavic medieval states for supremacy in the Balkans, the borders of the diocese were constantly changing, geographically the Archbishopric turned out to be part of different states, but retained autocephaly. The article reveals and characterizes the architectural originality of the monuments of the Ohrid Archbishopric in the context of historical, church-political and historical-architectural processes of the 13th–14th centuries, identifies its origins and traces the features of development, defines the role and place of this group of monuments in the broad context of late Byzantine architecture.This work is supported by the Russian Science Foundation (grant 20-18-00294-P) and done at the Research Institute of Theory and History of Architecture and Town Planning —  branch of the Central Research and Project Institute of the Construction Ministry of Russia.
Keywords: Ohrid; Kastoria; Prespa; the Archbishopric of Ohrid; byzantine architecture